A Rare Case of Congenitally Corrected Transposition of Great Arteries with Complete Heart Block - Rahman, Muhammed Mustafizur; Rahman, Md Arifur; Siddique, Md Abu; Ahmed, Md Khurshed; Uddin Sultan, Md Ashraf (University Heart Journal, 2012)
DOI: http://dx.doi.org/10.3329/uhj.v7i1.10212 UHJ 2011; 7(1): 53-55